The relationship between problematic online game usage, depression, and life satisfaction among university students - Zuhtiye Nur Yazici; Hatice Kumcagiz (ÜNİVERSİTEPARK Limited, 2021)
Background/purpose - In this study, the relationship between problematic online game usage, and depression and life satisfaction levels of university students was examined. Materials/methods - The research was conducted according to the relational screening model, with a sample consisting of 401 university students. The research data were obtained using the Beck Depression Inventory, the Problematic Online Game Use Scale, the Contentment with Life Assessment Scale, and a Personal Information Form prepared by the researchers. The data obtained were analyzed using Pearson Correlation Analysis, Independent Sample t-test, and One-Way Analysis of Variance (ANOVA). Results - The results of the study show that the relationship between students' use of problematic online games and their depression levels to be moderately positive, and revealed a low-level, negative relationship between life satisfaction levels. In addition, students' problematic online game use, depression, and life satisfaction levels were analyzed according to the variables of gender and grade level, and statistically significant differences were found to exist between them. Conclusion - The study's results revealed that as the use of problematic online games increased, the university students' depression levels increased in parallel, and that the depression levels of female students were higher than for their male counterparts. Lastly, it was observed that as the university students' use of problematic online games increased, their life satisfaction levels decreased.